Avaliação das propriedades furtiva e antitumoral de lipossomas revestidos com carboidratos contendo doxorrubicina - Aline Teixeira Maciel e Silva (2018)
Liposomal formulations used in the past, known as conventional liposomes, have circulating half-life time of only a few minutes, because they are rapidly absorbed by the Monocytic Phagocytic System (SMF) cells. Thus, liposomes known as stealth, long circulating or sterically stabilized were developed to improve circulation time. This purpose is generally achieved by the incorporation of hydrophilic polymers such as PEG and its derivatives. However, it is observed that these liposomes also present a high uptake rate by macrophages rich tissues, even though PEG-derived polymers are used. In addition, recent studies show that, when administered at sequential time intervals, PEGylated liposomes have a reduction in circulation time and an increase in the hepatic and splenic accumulation. These characteristics represent a barrier for the research of liposomal formulations and their clinical use. Thus, in the present work the coating of liposomes with carbohydrate derivatives was proposed in order to obtain nanostructures with longer circulation time. For this, synthesis of three trimeric glycosyltriazoles, derived from D-glucose, D-galactose, and Nacetylglicosamine were generated, and were coupled to 3-O-(2-aminoethyl)cholesterol via amide formation. The produced liposomes showed high encapsulation of doxorubicin, sustained release profile of the drug and good storage stability. The 99mTc-cholesterol-DTPA complex was also obtained and used in radiolabeling experiments with high yields and radiochemical stability. It was verified through clearance studies that the glycosylated liposomes presented a half-life of circulation superior to the pegylated liposomes. Hepatic targeting was also observed for galactosylated liposomes. Cell viability studies using 4T1 breast cancer cell line demonstrated higher cytotoxicity to carbohydrate-coated liposomes compared to pegylated liposomes. In vivo antitumor activity studies indicated increased efficacy of glucose-coated liposomes containing doxorubicin compared to pegylated liposomes and free doxorubicin. Indications of toxicity reduction for glycosylated liposomes were also observed. All these results together suggest that use of carbohydrates on the surface of the nanostructures can be a promising alternative to increase the vesicle circulation time to target liposomes to specific sites and, as a consequence, to increase the efficiency of the treatment with reduction of the toxicity.